A Brutal Hack: Tyranny, Rape, and the Barbarism of Bad Poetry in Ovid's Pyreneus Episode. (2020) - Cowan, Robert
Abstract: Poet-figures in Ovid's Metamorphoses have been the object of much study, especially those silenced by the powerful, but little attention has been given to Pyreneus. Immediately before the famous contest of the Muses and Pierides, the former briefly narrate their attempted rape by the usurping Thracian tyrant Pyreneus and his precipitous death while trying to fly after them. The few critics who have touched on this episode have tended to focus exclusively on one aspect, be it the poetic, sexual, political, or religious. None has provided a holistic interpretation which does justice to the complex interplay of these four dimensions or to Ovid's witty and characteristic reification of figurative language. Pyreneus is simultaneously an invading usurper, an attempted rapist, an impious theomach, and, on the poetic plane, a talentless plagiarist or derivative imitator, who tries to appropriate others' work but bathetically and disastrously fails. The interrelation of these four roles, each troping the others, throws light on all, and Pyreneus needs to be contextualized among the Met. 's other tyrants, rapists, and theomachs, as well as its poet-figures. The episode itself, derivative and overstuffed with Ovidian motifs, is mimetic of the sort of narrative bad (would-be) poets like Pyreneus produce.